Huanglongbing disease and quality of pectin and fruit juice extracted from Valencia oranges. (September 2020) - Koh, Jeewon; Morales-Contreras, Blanca Elizabeth; Guerra-Rosas, María Inés; Osorio-Hernández, Eduardo; Culver, Catherine A.; Morales-Castro, Juliana; Wicker, Louise
Abstract: Pectin is a co-product from juicing and the physico-chemical quality is important to functionality of pectin in food and pharmaceutical applications. Juice and peel from Huanglongbing (HLB) control and infected Valencia oranges were analyzed. Infected fruit had smaller diameter, lower L* and b* values and highly variable a* values. Juice from infected fruit had higher pectinmethylesterase (PME) activity of 1.5 Units/mL, which retained higher activity during 15 days of storage at 4 °C, and juice had higher cloud loss. Also, the juice obtained from infected fruit had lower °Brix (8.5–8.9), higher titratable acidity (0.71–0.88%), and lower pH (3.45–3.75). Molecular weights of 154–157 kDa and degrees of esterification of 65–67% were similar. Pectin yield from dried peel was reduced by 6% in infected fruit to 4.18 g/100 g. Total neutral sugars in pectin from control fruit were higher, 84.1 μg/mg, compared to infected fruit, 60.7 μg/mg. Glucose, galactose, and arabinose, were higher in control fruit, 25.0, 40.8, and 9.7 μg/mg, compared to 14.5, 27.4, and 8.3 μg/mg in infected fruit. Viscosity was 0.015 Pa s, in 1% pectin from control or infected fruit (p > 0.05). Juice quality, including cloud stability, was negatively impacted by HLB, however pectin functionality was minimally impacted. Highlights: Huanglongbing negatively impacts citrus juice ◦Bx, pH, titratable acidity, color. Juice from infected fruit has higher pectinmethylesterase activity and cloud loss. Lower yield of pectin from peel was obtained from infected fruit. Pectin is similar in control or infected fruit.